Worth a try: A statistical analysis of Brian O'Driscoll's contribution to the Irish rugby team - Pete Lunn; David Duffy (The Economic and Social Research Institute (ESRI), 2014)
The unique characteristics of Brian O'Driscoll's international rugby career provide a rare opportunity to obtain a measure of the impact of an individual player on the outcome of a team game. Generally, small samples and selection bias make such estimates unreliable. O'Driscoll, however, was an automatic selection for games against frontline opposition for 15 years, during which he missed a proportion of matches through injury. We model his impact on Ireland's results, treating injury as a random event and controlling for home advantage and the strength of the opposition. We find that O'Driscoll's presence was worth 6-7 points per game. We also find that he was particularly influential in close games, increasing the probability of victory by more than home advantage, both during the earlier and later parts of his career. Our models suggest that no other Irish player during the period made such a contribution, although they do indicate that some half-backs were similarly influential in close games.
Keywords: 330